Comparison of Diagnostic Accuracy of Cord Blood TSH and 3rd Day Venous Blood TSH in Screening Congenital Hypothyroidism: A Cross-sectional Study - Vinaykumar P Hedaginal; Rajdeep Pal; Neelu Elon; Mumtaz Sharif; Amit Saxena (Indian Journal of Neonatal Medicine and Research)
Introduction: Neonatal screening for Congenital Hypothyroidism (CH) is necessary, as it is one of the most common disorders related to mental impairment and growth retardation in newborns. Screening for CH can be conducted through either cord blood testing or venous blood testing. The accuracy of these tests in screening for CH is important for clinicians. Aim: To compare the diagnostic accuracy of cord blood Thyroid Stimulating Hormone (TSH) with day 3 venous blood sample TSH estimation in screening for CH and to estimate the incidence of CH in full-term neonates. Materials and Methods: The present cross-sectional study conducted in the Department of Paediatrics, Dr. D.Y. Patil Medical College, Navi Mumbai, Maharashtra, India, from April 2021 to October 2022. Term newborns born to euthyroid mothers were screened for CH at birth to analyse the cord blood TSH levels, and a repeat TSH estimation was performed on the 3rd postnatal day for those with abnormal values. Neonates with day 3 TSH levels greater than 10 mIU/L were subjected to a repeat thyroid function test at two weeks of life; persistence of elevated TSH levels was considered indicative of CH. The values were statistically analysed. Sensitivity, specificity, Positive Predictive Value (PPV), Negative Predictive Value (NPV) and diagnostic accuracy were calculated. Results: A total of 1,066 term newborns were screened for CH. The mean±Standard Deviation (SD) maternal age was 27.34±4.52 years. The male-to-female ratio among neonates was 1.5:1. Out of these 1,066 newborns, 100 had cord blood TSH levels greater than 10 mIU/L. Among these 100 newborns, 19 had day 3 TSH levels greater than 10 mIU/L. Of these 19 newborns, three were diagnosed with CH upon further follow-up at two weeks. The incidence of CH was three cases in 1,066 newborns. The diagnostic accuracy of cord blood TSH with cut-offs of greater than 10 mIU/L and greater than 20 mIU/L was 18% and 75%, respectively. In contrast, the diagnostic accuracy of day 3 TSH with the same cut-offs was 85% and 98%, respectively. Conclusion: Venous blood TSH has a higher accuracy in screening for CH than cord blood TSH; however, it requires an invasive prick and a three-day hospital stay.